Social and Cultural Elements Associated with Neurocognitive Dysfunctions in Spinocerebellar Ataxia Type 2 Patients - Mercadillo, Roberto Emmanuele; Galvez, Víctor; Díaz, Rosalinda; Paredes, Lorena; Velázquez-Moctezuma, Javier; Hernandez-Castillo, Carlos R.; Fernandez-Ruiz, Juan (Frontiers in Psychiatry, 2015)
Spinocerebellar Ataxia Type 2 (SCA2) is a rare genetic disorder producing cerebellar degeneration and affecting motor abilities. Neuroimaging studies also show neurodegeneration in subcortical and cortical regions related to emotional and social processes. From social neuroscience it is suggested that motor and social abilities can be influenced by particular cultural dynamics so, culture is fundamental to understand the effect of brain related alterations. Here we present the first analysis about the cultural elements related to the SCA2 disorder in 15 patients previously evaluated with neuroimaging and psychometric instruments, and their nuclear relationships distributed in six geographical and cultural regions in Mexico. Ethnographic records and photographic and video archives about the quotidian participant’s routine were obtained from the patients, their relatives and their caregivers. The information was categorized and interpreted taking into consideration cultural issues and patients’ medical files. Our analyses suggest that most of the participants do not understand the nature of the disease and this misunderstanding favors magic and non-medical explanations. Patients’ testimonies suggest a decrease in pain perception as well as motor alterations that may be related to interoceptive dysfunctions. Relatives’ testimonies indicate patients’ lack of social and emotional interests that may be related to frontal, temporal and cerebellar degeneration. In general, participants use their religious beliefs to deal with the disease and only a few of them trust the health system. Patients and their families are either openly rejected and ignored, tolerated or even helped by their community accordingly to different regional traits. We propose that ethnography can provide social representations to understand the patients’ alterations, to formulate neurobiological hypotheses, to develop neurocognitive interventions, and to improve the medical approach to the disease.